Conceptualisation and Validation of Multidimensional Measure of Workplace Spirituality. (June 2022) - Saxena, Anubhuti; Prasad, Asha
Workplace spirituality (WPS) has gained acknowledgement as a significant discipline in the corporate world. The dynamic environment leaves all the organisations in a quandary as to how to manage and take relevant and ethical decisions at the same time. However, despite the unprecedented challenges, organisations need to continuously stay agile, innovate for self-development and growth, and ultimately augment the wealth of the nation. It is at this time that WPS acquires utmost importance for the leaders. The research article intends to develop a scale and add new dimensions to the literature for measuring WPS from the point of view of the existing bank employees. We conducted two studies for testing the scale. For conducting Study 1, we applied exploratory factor analysis (EFA) with varimax rotation, and for Study 2, we applied second-order confirmatory factor analysis (CFA). Statistics were drawn from 406 employees from banks in Delhi National Capital Region (NCR). The results showed that WPS has seven dimensions, namely, meaningfulness, compassion, gratitude, authenticity, embracing diversity, resilience and inner peace, and others' orientation. It may be useful for managers to analyse these dimensions in detail in order to identify their impact on employee work attitudes and job outcomes. We believe that this is a pioneering wherein WPS has been represented as a second-order factor. The concluding part of this paper contains an incisive discussion on future developments in the spirituality domain.